PENGEMBANGAN MEDIA WEBSITE LAYANAN INFORMASI TERHADAP PERENCANAAN KARIER SISWA KELAS IX SMP ISLAM AL-HUSNA MADANI - Riana Listiyani Khoerunisa; Heris Hendriana; Tuti Alawiyah (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Website creation as a source of information on career planning for 9th grade students at Al-Husna Madani Islamic High School. In improving career planning skills, students must know their abilities, intelligence, interests, talents that match their abilities and potential. It is important to ensure that mistakes are avoided in assessing future career plans. This study uses the research and development method outlined by Borg and Gall, with the aim of creating a product that has gone through a feasibility test by various expert validators, including media experts, subject matter experts, and practitioners. Study participants included a group of 10 students for the initial trial and a group of 20 students for the comprehensive trial, all students enrolled at Al-Husna Madani Islamic High School and experiencing difficulties related to career planning. The results of the media expert validation were 80.21%, material experts 82.78%, practitioner experts 90.83%, limited student validation results 92.70% and broad student validation results 91.02% which if averaged the results from the various validators showed that this website reached a percentage of 91.86%. Based on these results, it is very clear that there is a high level of eligibility for use, with the condition of completing the revision process. The development of this website encourages students to take an active role in determining their career paths individually. This will facilitate the career decision-making process for students.